O78: SARCOPENIA IN LOCALLY ADVANCED BREAST CANCER: PREVALENCE, AND IMPACT ON CLINICAL AND ONCOLOGIC OUTCOMES. (27th April 2021) - Collins, PM; Elliott, JA; Brennan, MJ; McNamara, M; O'Malley, E; Barry, K; Sweeney, K; Malone, C; Lowery, A; McLaughlin, R; Kerin, MJ
Abstract: Introduction: Sarcopenia in cancer may confer negative outcomes, but its prevalence and impact in the modern multimodal management of locally advanced breast cancer have not been systematically studied. Method: Patients undergoing neoadjuvant therapy and surgery for locally advanced breast cancer between 2010 and 2015 were studied. Skeletal muscle index (SMI) and lean body mass (LBM) were determined. Sarcopenia was defined by computed tomography (CT) at L3 as SMI<38.5cm 2 /m 2 . Multivariable linear, logistic, and Cox regression analysis was undertaken to determine the independent impact of sarcopenia on clinical and oncologic outcome. Result: 258 patients were studied. Sarcopenia was present in 23.0%, 7.8% and 0.0% of patients with normal weight, overweight and obesity, respectively ( P =0.001). Sarcopenia was not associated with baseline cT and cN stage, tumour grade, histologic type or receptor status. Patients with sarcopenia exhibited equivalent indices of neoadjuvant therapy response including ypT and ypN stage, pathologic complete response and Sataloff grade following surgical resection. Postoperatively, sarcopenia was not independently associated with comprehensive complications index ( P =0.242), length of stay ( P =0.716) or overall morbidity ( P =0.365). However, on multivariable analysis, lower LBM independently predicted reduced invasive disease-free ( P =0.049, HR0.93[95%CI0.87-1.00]) and overall ( P =0.028, HR0.92[0.85-0.99]), but not disease-specific survival ( P =0.070). Conclusion: Consistent with a lack of association with baseline and post-treatment pathologic features, sarcopenia in locally advanced breast cancer is associated with reduced overall, but not disease-specific, survival. These data indicate that the prognostic impact of sarcopenia may be mediated by impaired performance status and increased non-cancer mortality. Take-home message: Consistent with a lack of association with baseline and post-treatment pathologic features, sarcopenia in locally advanced breast cancer is associated with reduced overall, but not disease-specific, survival. These data indicate that the prognostic impact of sarcopenia may be mediated by impaired performance status and increased non-cancer mortality.